2019
DOI: 10.1021/acsami.9b00037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Mg(CB11H12)2 and Mg(TFSI)2 at the Magnesium/Electrolyte Interface

Abstract: An essential requirement for electrolytes in rechargeable magnesium-ion (Mg-ion) batteries is to enable Mg plating−stripping with low overpotential and high Coulombic efficiency. To date, the influence of the Mg/ electrolyte interphase on plating and stripping behaviors is still not well understood. In this study, we investigate the Mg/ electrolyte interphase from electrolytes based on two Mg salts with weakly coordinating anions: magnesium monocarborane ( M g ( C B 1 1 H 1 2 ) 2 ) a n d m a g n e s i u m b i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 42 publications
9
99
0
Order By: Relevance
“…Therefore, the structure of magnesium electrolytes is highly influenced by both the solvent and the salt used. Due to the environmental issues and problems with current collector corrosion, much effort has been placed on the development of Cl À -free electrolytes; [11][12][13][14] however, the best performance is still achieved when chlorine anions are included in the system. [7,[15][16][17] Their presence induces MgÀ Cl bonding structures that are considered to be responsible for the success of the electrode processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the structure of magnesium electrolytes is highly influenced by both the solvent and the salt used. Due to the environmental issues and problems with current collector corrosion, much effort has been placed on the development of Cl À -free electrolytes; [11][12][13][14] however, the best performance is still achieved when chlorine anions are included in the system. [7,[15][16][17] Their presence induces MgÀ Cl bonding structures that are considered to be responsible for the success of the electrode processes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, longer glymes, up to tetraglyme (G4), have been used successfully, although some increase in overpotential is observed. [12,22,23] In general, an increase in glyme length gives a (desired) lower volatility of the electrolyte, but at the cost of higher viscosity and slower transport kinetics. [22,[24][25][26] Undoubtedly, that also affects the induced structure of the complexes and the reached equilibrium, which is crucial for magnesium electrolytes, determining many parameters, including the battery lifetime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies of Mg (TFSI) 2 /DME electrolyte demonstrated that there was a high overpotential for both Mg deposition (0.6 V) and stripping (1.5 V) using this electrolyte (Shterenberg et al, 2015). The high overpotential in Mg (TFSI) 2 electrolyte was attributed in some studies to the TFSI − anion's instability at the Mg anode which causes it to degrade and form MgS as well as MgF 2 (Yoo et al, 2017;Ding et al, 2018;Jay et al, 2019). Electrolytes containing the Mg (TFSI) 2 salt also demonstrate sensitivity to water, which can aid solvent decomposition (Yu et al, 2017) and passivate the Mg anode interface (Bachhav et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among the common weakly coordinating anions, bis(trifluoromethanesulfonyl)imide (TFSI -) may possess the highest dissociation constant, however, it is known that TFSIcan be reduced electrochemically and chemically by metals including Al. [16][17][18][19] On the other hand, PF6anion strikes a good balance between dissociation constant and mobility as well as stability. 20 In this study, we report the synthesis of electrochemical properties of Al(PF6)3 for the first time.…”
Section: N Introductionmentioning
confidence: 99%